Silver(I)-Promoted Conversion of Thioamides to Amidines: Divergent Synthesis of a Key Series of Vancomycin Aglycon Residue 4 Amidines that Clarify Binding Behavior to Model Ligands - Okano, Akinori (2012)
Development of a general Ag(I)-promoted reaction for the direct conversion of thioamides to amidines is disclosed. This reaction was employed to prepare a key series of vancomycin aglycon residue 4 substituted amidines that were used to clarify their interaction with model ligands of peptidoglycan precursors and explore their resulting impact on antimicrobial properties.